Infrared spectra of carbocations and CH4+ in helium. Issue 48 (6th December 2021) - Davies, Julia A.; Yang, Shengfu; Ellis, Andrew M.
Abstract : Infrared (IR) spectra of rigid and fluxional carbocations have been measured at low temperatures (≤10 K) following electron ionization of superfluid helium nanodroplets doped with methane, and an IR spectrum for CH4 + is presented for the first time. Abstract : Infrared (IR) spectra of several hydrocarbon cations are reported, namely CH3 +, CH4 +, CH5 +, CH5 + (CH4 ) and C2 H5 + . The spectra were generated from weakly-bound helium-cation complexes formed by electron ionization of helium nanodroplets doped with a neutral hydrocarbon precursor. Spectroscopic transitions were registered by photoexcitation of the complexes coupled with mass spectrometric detection of the bare ions. For CH3 +, we provide evidence showing that the helium-bound complexes contain 10–20 helium atoms (on average) and have a rotational temperature of ∼5 K. We show that this technique is well-suited to the study of highly symmetric or fluxional ionic species, as these intrinsic properties are preserved in the helium environment. This is in contrast to conventional tagging methods that use a single atom or molecule, which can change the point group or rigidity of the core ion and therefore the spectral profile. We demonstrate this for the highly fluxional molecular ion CH5 +, whose spectrum in the current study matches that of the gas phase ion, whereas the fluxionality is lost when a methane tag is added. Finally, we present the first IR spectrum of methane cation, CH4 + . The spectrum of this fundamental organic ion shows CH stretching bands consistent with a non-tetrahedral structure, a consequence of Jahn–Teller distortion.